Interactions of Cisplatin with non-DNA Targets and their Influence on Anticancer Activity and Drug Toxicity: The Complex World of the Platinum Complex - Mezencev, Roman (Current Cancer Drug Targets, 2014)
Since the discovery of its anticancer activity in 1970s, cisplatin and its analogs have become widely used in clinical practice, being administered to 40-80% of patients undergoing chemotherapy for solid tumors. The fascinating story of this drug continues to evolve presently, which includes advances in our understanding of complexity of molecular mechanisms involved in its anticancer activity and drug toxicity. While genomic DNA has been generally recognized as the most critical pharmacological target of cisplatin, the results reported across multiple disciplines suggest that other targets and molecular interactions are likely involved in the anticancer mode of action, drug toxicity and resistance of cancer cells to this remarkable anticancer drug. This article reviews interactions of cisplatin with non-DNA targets, including RNAs, proteins, phospholipids and carbohydrates in the context of its pharmacological activity and drug toxicity. Some of these non-DNA targets and associated mechanisms likely act in a highly concerted manner towards the biological outcome in cisplatin-treated tumors; therefore, the understanding of complexity of cisplatin interactome may open new avenues for modulation of its clinical efficacy or for designing more efficient platinum-based anticancer drugs to reproduce the success of cisplatin in the treatment of highly curable testicular germ cell tumors in its therapeutic applications to other cancers.
Keywords: BRCA1